Validation of Ctenitis jinfoshanensis (Dryopteridaceae) and Lepisorus simulans (Polypodiaceae) for fern flora of China - Duan, Yi-Fan; Zhang, Libing (Phytotaxa, 2015)
As the largest finished floristic project, the Flora of China documents 31,362 species of vascular plants, of which 2,129 species are ferns and lycophytes (Lin et al. 2013, Wu et al. 2013, Zhang & Gilbert 2015). While working on a revision of the fern genus Ctenitis C.Christensen (Dryopteridaceae; Smith et al. 2006, Liu et al. 2007, Zhang et al. 2013) in the Old World, we happened to find that two unrelated names published in a same article by Ching & Liu (1984), Ctenitis jinfoshanensis Ching & Z.Y. Liu and Lepisorus simulans Ching & Z.Y. Liu (Polypodiaceae), were not validly published, because two gatherings were designated as types for each name (Art. 40.2; McNeill et al. 2012). In fact, the type designations of each name were conducted twice in Latin and Chinese by the authors, respectively, and each time a different gathering was designated as type. Here we validate the two names by choosing one gathering as the type for each name.